The Al-Attas Concept of Justice in Sharia Economic Law: Countering Patronage Culture through an Islamic Political Economy Approach to Economic Sustainability in Indonesia - Nur Majdina; Taufiq Ramadhan; Firda Inayah; Ratih Ayu Mufliha (IQTISHODUNA: Jurnal Ekonomi Islam, 2026)
This study investigates the implementation of Syed Muhammad Naquib al-Attas' concept of justice within Islamic economic law as a strategy to overcome the culture of patronage for the sustainability of the Indonesian economy. It aims to fill a literature gap by integrating al-Attas philosophical framework into an analysis of Indonesia's economic system. The research employs a systematic literature review (SLR) guided by the PRISMA protocol, with searches conducted in the Scopus database using relevant keywords. From 238 identified articles, 73 met the inclusion criteria for thematic analysis. The results reveal three primary findings. First, al-Attas' concept of justice, which emphasizes distributive justice, transparency, and the avoidance of exploitation, provides a robust philosophical foundation for Islamic economic law. Second, the deeply ingrained patronage culture acts as a major structural obstacle to realizing these justice principles, fostering social and economic inequality. Third, integrating Islamic values with sustainability principles such as the circular economy offers a holistic solution to contemporary challenges. The discussion underscores the need for interdisciplinary approaches and the leveraging of digital technology to enhance accountability and public participation. In conclusion, applying al-Attas' concept of justice holds significant potential for fostering a more inclusive and sustainable economic system. The practical implications call for policy reforms that align Sharia principles with sustainable development goals. However, this review is limited by its reliance on a single database (Scopus) and the predominance of conceptual rather than empirical studies, which may restrict the generalizability of the findings Future research should empirically test this framework using quantitative methods and further explore the role of technology in strengthening Islamic economic governance.